Application of a new hydrocarbon detection technique with phase decomposition in carbonate reservoir of the Pre-Caspian Basin - Wang, Zhen; Zhang, Yiqiong; Ji, Zhifeng; Jin, Shutang; Jiang, Ren; Wang, Xueke; Wang, Yankun; Sheng, Shanbo; Lin, Yaping (Frontiers in Earth Science, 2023)
Due to the low porosity and thin thickness of the Carboniferous carbonate reservoir in the Pre-Caspian Basin, the impedance difference between the reservoir and the surrounding rock is not obvious, and the seismic response characteristics are weak. It is ambiguous to detect oil and gas based on the convention attribute amplitude and frequency information. According to the geological characteristics of the Carboniferous Reservoir in the Pre-Caspian Basin, we proposed a new hydrocarbon detection method from the phase decomposition of sensitive frequency in post-stack seismic data, which improves the accuracy of hydrocarbon detection. The forward model is utilized to testify the feasibility of hydrocarbon detection with phase decomposition, which showed that the amplitude of oil and gas layers in specific phase components is stronger than that of water layer. The special frequency band seismic data sensitive to oil and gas is decomposed into different phase components, and then hydrocarbon is detected according to the amplitude anomaly in specific phase components. The application of forward model and filed example demonstrates that the fluid type in the reservoir can be directly identified by the phase decomposition technique, which has higher accuracy than the conventional hydrocarbon detection technology with post-stack data. After the application of this technology, the coincidence between hydrocarbon results and oil test results in the block was increased from 60% to 80%, and the coincidence rate is much higher than the detection results using conventional attributes, more than 90%. All the two exploration wells deployed according to the detection results have obtained higher oil production, new discovered oil geologic reserves have been increased to 5.54 million tons.